CONFESSIONAL FACTOR IN THE SOCIO-POLITICAL AND PARTY-POLITICAL PROCESS OF THE MODERN RUSSIAN FEDERATION - M. A. Astvatsaturova; A. S. Kshov (Современная наука и инновации, 2022)
The article is devoted to identifying the accentuation of the confessional factor in the socio-political process of the Russian Federation against the background of its stabilization and stagnation vectors. There are trends in including the confessional factor in the official discourse of state leaders, the position of the head of the Russian state in relation to religion, faith, and the role of religious institutions. Political programs and discourse of political leaders in relation to the role, goals and tasks of religious institutions are analyzed.